Understanding FX Liquidity - Karnaukh, Nina; Ranaldo, Angelo; Söderlind, Paul (Review of Financial Studies, 2015)
Previous studies of liquidity in the foreign exchange (FX) market span short time periods or focus on specific measures of liquidity. In contrast, we provide a comprehensive study of FX liquidity and commonality over more than two decades and a cross-section of forty exchange rates. After identifying the most accurate liquidity proxies based on low-frequency and readily available data, we show that commonality in FX liquidities is stronger for developed currencies and in highly volatile markets. We also show that FX liquidity deteriorates with risk in stock, bond and FX markets, and that riskier currencies are more exposed to liquidity drops.